2002
DOI: 10.1089/10799900260100196
|View full text |Cite
|
Sign up to set email alerts
|

The Detection of IRF-1 Promoter Polymorphisms and Their Possible Contribution to T Helper 1 Response in Chronic Hepatitis C

Abstract: We described the interferon (IFN) regulatory factor-1 (IRF-1) promoter single nucleotide polymorphisms (SNPs), and the clinical and immunologic implications of these SNPs have been investigated. We successfully determined the mutation at -300 of the IRF-1 promoter by polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP), and this mutation linked with other mutations in the promoter region. In our Japanese population, the frequency of the type -300*A/A was 11.9%, type A/G was 54.2%, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
2
1

Year Published

2004
2004
2009
2009

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 30 publications
1
13
2
1
Order By: Relevance
“…Polymorphisms in the promoter region may affect the transcriptional activation of IRF-1 and its subsequent expression. Supporting evidence comes from a study that demonstrated that a particular promoter polymorphism (SNP at À300G/A) was shown to be correlated with cellular immunity to HIV infection (Saito et al 2002). Our data demonstrates that promoter polymorphism is common in the Kenyan IRF-1 gene sequences.…”
Section: Resultssupporting
confidence: 63%
See 2 more Smart Citations
“…Polymorphisms in the promoter region may affect the transcriptional activation of IRF-1 and its subsequent expression. Supporting evidence comes from a study that demonstrated that a particular promoter polymorphism (SNP at À300G/A) was shown to be correlated with cellular immunity to HIV infection (Saito et al 2002). Our data demonstrates that promoter polymorphism is common in the Kenyan IRF-1 gene sequences.…”
Section: Resultssupporting
confidence: 63%
“…The genotype and allelic frequencies of each SNP were calculated and depicted in Table 2. Twenty-seven of these SNPs have been previously reported either in publications or by the International Human Genome Sequencing Consortium through the NCBI-based SNP database (Database1;Database2;Donn et al 2001;Nakao et al 2001;Noguchi et al 2000;Saito et al 2001Saito et al , 2002. A number of previously reported SNPs were not observed in the subjects from this study, including 5551T/G, 4950A/G, 5558T/C, 5636G/A, 7662C/-and 6355G/A, demonstrating the high degree of IRF-1 genetic polymorphism in different ethnic populations.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There are, however, many factors that influence the success of IFN and RBV combination therapy. The resistance or sensitivity to IFN or peg-IFN, not to RBV, might also affect the early viral response, and many factors in both viral and host sides are known to affect IFN responsiveness, such as NS5A mutations [Enomoto et al, 1996], immunological status [Saito et al, 2000], or irf-1 gene promoter polymorphisms [Saito et al, 2002. Together, these factors might determine the efficacy of anti-viral therapy in vivo, and the present in vitro data provides evidence partially supporting our clinical observations that NS5B polymorphisms are associated with early viral clearance during IFN and RBV therapy.…”
Section: Discussionmentioning
confidence: 99%
“…19 Furthermore, polarization toward the Th1 phenotype by in vitro or in vivo administration of type I IFN was more pronounced in individuals carrying the A/A single nucleotide polymorphism (SNP) at position Ϫ300. 20,21 Based on the central role of IFN-␣ in both the development of psoriasis and Th1 polarization, combined with the role of the IRF-1 promoter SNPs on the extent of IFN-␣-induced Th1 skewing, we hypothesized that IFN-␣ stimulation of psoriatic peripheral blood mononuclear cells (PBMC) results in a more pronounced Th1 polarization due to SNPs in the IRF-1 promoter. To test this, PBMCs from healthy donors and psoriasis patients were cultured for 24 h in the presence or absence of 500 U/mL IFN-␣, and the concentration of prototypic type 1 (IFN-␥ and IL-12p40) and type 2 (IL-10 and IL-4) cytokines was measured in the culture supernatant by ELISA.…”
mentioning
confidence: 99%